2005
DOI: 10.1007/s11274-004-1005-2
|View full text |Cite
|
Sign up to set email alerts
|

Purification of lipase from Cunninghamella verticillata by stepwise precipitation and optimized conditions for crystallization

Abstract: Lipase from the oil-mill waste isolate Cunninghamella verticillata was purified by stepwise precipitation using acetone, as a sequel to our earlier conventional column chromatographic method [Gopinath et al. (2002) World Journal of Microbiology and Biotechnology 18, 449-458]. The yield of purified lipase was approx. 4-fold higher than by the previous method and the purified lipase was obtained with 70-80% acetone saturations. The enzyme was resolved as a single band with homogeneity both by native and by SDS-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 22 publications
0
5
0
2
Order By: Relevance
“…For such enzymes, surface pressure and lipid distribution have been reported to affect substrate specificity and activity (Jaeger et al, 1994) by substrate-binding interactions (Hiol et al, 1999). At 81.3 kDa, the molecular weight of the N. rileyi lipase much higher than those reported for several other fungal lipases (Kumarevel et al, 2005) including those of C. verticillata (49 kDa) (Gopinath et al, 2002), Y. lipolytica (38 kDa) (Yu et al, 2007), R. oryzae (32 kDa) (Hiol et al, 2000), A. carneus (27 kDa) (Saxena et al, 2003) and Pichia burtonii (51 kDa) (Sugihara et al, 1995).…”
Section: Discussionmentioning
confidence: 97%
“…For such enzymes, surface pressure and lipid distribution have been reported to affect substrate specificity and activity (Jaeger et al, 1994) by substrate-binding interactions (Hiol et al, 1999). At 81.3 kDa, the molecular weight of the N. rileyi lipase much higher than those reported for several other fungal lipases (Kumarevel et al, 2005) including those of C. verticillata (49 kDa) (Gopinath et al, 2002), Y. lipolytica (38 kDa) (Yu et al, 2007), R. oryzae (32 kDa) (Hiol et al, 2000), A. carneus (27 kDa) (Saxena et al, 2003) and Pichia burtonii (51 kDa) (Sugihara et al, 1995).…”
Section: Discussionmentioning
confidence: 97%
“…A reversed micellar system, membrane processes, immunopurification, hydrophobic interaction chromatography with an epoxy-activated spacer arm (ligand), column chromatography using polyethylene glycol (PEG)/sepharose gel, and aqueous two-phase systems are also recommended [81]. Kumarevel et al [82] reported a stepwise purification strategy for fungal lipases to remove other components released from the fungus Cunninghamella verticillata extracellularly, using acetone precipitation as the important step. To avoid many steps in this study and to minimize the impurities as much as possible the experiment was repeated with 50% acetone saturation with a gradual increments of 5% acetone.…”
Section: Purification Strategies For Lipasesmentioning
confidence: 99%
“…Using the Box-Behnken design, conditions were optimized for lipase production by Geotrichum candidum [34] and optimization of purified lipase from Cunninghamella verticillata for physical parameters was also shown [40]. Using these optimized conditions, the purification steps were reduced and purified lipase was used for crystallization studies [82]. Other than Box-Behnken, the Plackett-Burman design and the Luedeking-Piret model can also be used for different optimization studies.…”
Section: Statistical Calculationsmentioning
confidence: 99%
“…From these results, lipolytic activity (high and moderate activity) was evidenced using Tween-20 and tributyrin methods by 18 and 31 species, respectively, whereas the spectrophotometric method supported 20 species. All our earlier studies mainly rely on tributyrin plates and assay with 4-nitrophenyl palmitate to detect lipolytic activity (Gopinath 1998;Gopinath et al 2002Gopinath et al , 2003aKumarevel et al 2005).…”
Section: Lipolytic Activitymentioning
confidence: 99%